PENGARUH GOOD GOVERNMENT GOVERNANCE TERHADAP KINERJA PEGAWAI BADAN NARKOTIKA NASIONAL PROVINSI SUMATERA UTARA - Syahrina Yanti hasibuan; Nur Fadhilah Ahmad Hasibuan (Program Studi Akuntansi, Fakultas Ekonomi. Universitas Samudra, 2022)
This study aims to determine whether the indicators of Good Government Governance, namely participation, transparancy, accountability, effectiveness and law enforcement, have an influence on the performance of the employees of the natonal Narcotics Agency of North Sumatra.whether the indicators of Good Government Governance have a positive effect on the performance of the employees of the national Narcotics Agency of North Sumatra Provinsi. This research uss quantitive methods. Namely by collecting, presenting, analyzing, testing hypotheses and then making conclusions and suggestions. Samples were collected by simple random sampling method. Research data collection using a questionnaire to 30 employees.And will be processed through by SPSS version 25. The results of this study will conclude that there is an influence of Good Government Governance indicators on the performance of the employees of the national Narcotics Agency of North Sumatra Provinsi.